THE INVESTIGATION OF ELEMENTS AFFECTING CERTAIN MICROALG’S DEVELOPMENT AND POSSIBLE ANTIBACTERIAL PROPERTIES - Anwer, Sewgil S.; Ali , Ayad K.; Şule İnci (Science Journal of University of Zakho, 2024)
During the previous few decades, the pursuit has experienced an increase for novel marine-derived molecules with potential use in the pharmaceutical, human or animal nutrition, cosmetics, and bioenergy industries. The current study aimed at obtaining the optimum growth rate of some microalgal isolates and finding their antibacterial activity. The microalgae were purified in BG11 medium and the biomass extracted using ethanol, acetone, diethyl ether and methanol was then examined for antimicrobial activity by disc diffusion and minimum inhibitory concentration methods.The optimum growth rate obtained at pH 8, temperature 26-28 ℃, and 2000 lux for all algal isolates. All microalgae extracts showed antimicrobial activity against tested bacteria with different solvents. The higher antibacterial activity obtained with ethanol extracts while water extract showed low antibacterial activity. Chlorella sp. and Spyrogyra sp. showed higher antibacterial rather than other isolates. Overall, these results imply that microalgae extracts, particularly those from Spirogyra sp. and Chlorella sp., may be sources of antibacterial chemicals. To identify and describe the precise bioactive substances in charge of the reported inhibitory effects, additional study is required. Further research into the mechanisms of action, safety, and possible uses of these microalgae extracts in bacterial infection management would be advantageous